Foliar application of sulfur on postharvest traits of onion hybrids - Oliveira, Liomar Borges de; Casais, Luana Keslley Nascimento; Teles, Simone Pereira; Prolo, Tamara Thalia; Sousa, Allan Sales de; Paula, Carolina Pereira de; Cardoso, José Avelino; Nascimento, Ildon Rodrigues do (Comunicata Scientiae, 2025)
Onion is one of the most widely consumed seasoning vegetables in the world. Beyond productivity, onion quality is of great importance, influenced by factors such as appearance, aroma, flavor, and chemical composition. This study aimed to evaluate the effect of applying elemental sulfur at different growth stages on the postharvest quality attributes of onion bulbs. Two experiments were conducted at different times using a factorial design in randomized blocks. Four hybrids were tested: Diamantina®, Optima® F1, Serena® F1, and Gamay® F1 (purple). The second factor was the timing of foliar elemental sulfur application: at the development stages of 4–6 leaves, 6–8 leaves, 8–10 leaves, and 10–12 leaves, along with a control group that received solid elemental sulfur applied to the soil. The evaluated attributes included pungency (µmol.g-1), soluble solids (°Brix), total titratable acidity (% pyruvic acid), pH, leaf sulfur content, and bulb sulfur content. Among the traits measured, the pyruvic acid content was influenced by the timing of sulfur application, with the Serena® F1 hybrid at the 10–12 leaf stage showing significant differences from the other hybrids. Regarding pungency, the Diamantina®, Serena® F1, and Gamay® F1 hybrids were classified as having medium pungency when sulfur was applied foliarly, while the Optima® F1 hybrid was classified as low/sweet pungency. Sulfur content in the bulbs and leaves of the onion cultivars was not significantly affected by foliar sulfur application.